Evaluation of Distillers Dried Grains Plus Solubles as Protein Source in The Diets of Growing Crossbred Calves - Sihag, Sajjan (Indian Journal of Animal Nutrition, 2021)
A study was conducted to evaluate the effects of dried distillers grains plus solubles (DDGS) on the nutrient utilization and growth performance of crossbred calves. Twelve crossbred female calves (Holstein Friesian Ã— Haryana Ã— Sahiwal) were divided randomly into 3 groups viz: T1, T2 and T3 of 4 animals each, and were fed isocaloric and isonitrogenous diets according to NRC (2001) standards. Weighed quantities of wheat straw and green fodder were fed daily to each animal for an experimental period of 4 months. Mustard cake protein inthe concentrates of treatment T2 and T3 was replaced with DDGS protein at 75 and 100% levels, respectively. 75% replacement of mustard cake protein with DDGS protein did not caused any negative effect on digestibility of crude protein, crude fibre, organic matter and neutral detergent fibre, but inclusion of DDGS in place of all mustard cake reduced the digestibility of these nutrients significantly (P